2015
DOI: 10.4317/medoral.20644
|View full text |Cite
|
Sign up to set email alerts
|

The mandibular incisive canal and its anatomical relationships: A cone beam computed tomography study

Abstract: BackgroundTo avoid postoperative injuries in the interforaminal region, presence of the Mandibular Incisive Canal (MIC), its extension and canal positioning in relation to the cortical bone and alveolar process were investigated by cone beam computed tomography (CBCT). Material and MethodsOne hundred CBCT examinations obtained by means of the i-CAT CBCT imaging system were analyzed in multiple-plane views (axial, panoramic and cross-sectional) and three-dimensional representations were performed using iCAT CBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
5
18
0
2
Order By: Relevance
“…These findings corroborate those by Pires et al (17), who reported similar values for the initial and final portion of the MIC. According to studies from the United States (17), Iran (20), China (10), and Brazil (18), the MIC was closer to the buccal cortex than to the lingual cortex during its intraosseous path, and in agreement with the present study. Lim et al (19) reported that MIC deviated lingually from its starting point towards its endpoint in the mandible.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings corroborate those by Pires et al (17), who reported similar values for the initial and final portion of the MIC. According to studies from the United States (17), Iran (20), China (10), and Brazil (18), the MIC was closer to the buccal cortex than to the lingual cortex during its intraosseous path, and in agreement with the present study. Lim et al (19) reported that MIC deviated lingually from its starting point towards its endpoint in the mandible.…”
Section: Discussionsupporting
confidence: 92%
“…In relation to investigations that used different image acquisition protocols, Apostolakis and Brown (15) reported a mean CIM length of 8.9 mm, while the present study found a mean length of 7.7 mm. However, this length is higher than the values for the right (7.1 mm) and left (6.6 mm) sides reported by Pires et al (18). In addition, previous studies have reported relatively greater mean lengths for the MIC, including 9.97 mm (13) The smaller diameter and poorer corticalization of the MIC compared with the mandibular canal make its visibility a challenge.…”
Section: Discussionmentioning
confidence: 67%
“…Although the genial spinal canal is seldom described in anatomy textbooks, it is doubtless present in almost 100% of cases as confirmed by different investigations (Liang et al, 2006;Birkenfeld et al, 2015;Ferreira Barbosa et al, 2019;Gilis et al, 2019). In the literature, there is some confusion about the nomenclature of this structure in the mandible (He et al, 2017), possibly because there is no defined term for it in the official terminologia anatomica (FIPAT, 2011) In some publications, the term "incisive canal" is used (Serman, 1989;Jacobs et al, 2002;Mraiwa et al, 2003;Raitz et al, 2014;Pereira-Maciel et al, 2015;Ramesh et al, 2015;Gomes et al, 2018;Ferreira Barbosa et al, 2019;Gilis et al, 2019). However, that term refers to the maxillary incisor canal and according to the anatomical nomenclature is incorrect in the context of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some authors believe that the incisive nerve runs through the intramedullary spaces, and not within a bony canal, therefore, is not commonly detected by conventional radiography. 21,25 In fact, the same limitation can be valid for CBCT as well due to the lack of well-defined MIC in the anterior part of the mandible. 26 An incisive bundle can be seen as having complete, partial, or no cortical walls.…”
Section: Discussionmentioning
confidence: 99%